CHAOS ENGINEERING: STRENGTHENING FINANCIAL TRANSACTION SYSTEMS THROUGH CONTROLLED DISRUPTION - Sushant Sood (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
This comprehensive article explores the transformative role of chaos engineering in modern financial services, examining its impact on system resilience, operational stability, and risk management. The article investigates how financial institutions leverage controlled failure testing to enhance disaster recovery capabilities, maintain regulatory compliance, and strengthen customer trust. Through a detailed examination of implementation strategies, market dynamics, and performance metrics, this article demonstrates how chaos engineering has evolved from an experimental approach to an essential framework for building robust financial infrastructure. The article encompasses multiple aspects, including transaction processing improvements, system recovery mechanisms, and the economic benefits of proactive testing methodologies in financial systems.